2022
DOI: 10.1007/s40620-022-01418-6
|View full text |Cite
|
Sign up to set email alerts
|

Organizational support, training and equipment are key determinants of burnout among dialysis healthcare professionals during the COVID-19 pandemic

Abstract: Introduction Burnout was already found to be an important factor in the professional landscape of nephrology prior to the COVID-19 outbreak and is expected to worsen during the pandemic. Objectives The aim of our study was to assess pandemic experiences, perceptions, and burnout among Polish dialysis unit professionals in the COVID-19 period. Participants and methods A survey, which consisted of a Pandemic Experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…35 This has been exacerbated during the COVID-19 pandemic. 36 Our study also found HCPs' work stress reduced their capacity to take an active role in the trial, and thus work stress may impede implementation of new infection-prevention measures. However, McAlearney et al found that nurses' perspectives and action could improve implementation of a central-lineassociated BSI prevention initiative.…”
Section: Discussionmentioning
confidence: 57%
“…35 This has been exacerbated during the COVID-19 pandemic. 36 Our study also found HCPs' work stress reduced their capacity to take an active role in the trial, and thus work stress may impede implementation of new infection-prevention measures. However, McAlearney et al found that nurses' perspectives and action could improve implementation of a central-lineassociated BSI prevention initiative.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, patients on hemodialysis are vulnerable to Covid-19 infection due to associated comorbidities & insufficient immune system [9] . The prevention and control of COVID-19 in dialysis units is more difficult than in the general population and is particularly problematic due to frequent patient visits and shared use of the dialysis department [10] .…”
Section: Discussionmentioning
confidence: 99%
“…All nephrologists in this study noted the need for widespread systems change in response to COVID-19. This call for organizational support, improved training, and additional equipment were the conclusions of a subsequent study of burnout in nephrologists during the pandemic [48]. Fear of contagion increased when appropriate personal protective equipment was insufficient.…”
Section: Nephrologymentioning
confidence: 99%